1999
DOI: 10.1016/s0002-9440(10)65142-5
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Selectin Ligands on Colon Carcinoma Mucins Can Mediate Pathological Interactions among Platelets, Leukocytes, and Endothelium

Abstract: Many interactions that occur among leukocytes, platelets, and endothelial cells in the vasculature have been shown to be mediated by the selectin family of cell adhesion molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
134
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(138 citation statements)
references
References 53 publications
3
134
0
1
Order By: Relevance
“…E-, P-, and L-selectins are vascular receptors for certain normal sialyl Lewis x/a containing mucin-type glycoproteins found on leukocytes and endothelium (40)(41)(42)(43). Because selectins can mediate tumor cell interactions with platelets, leukocytes, and endothelium in vitro (39,44,45), an in vivo role for selectins in the metastatic spread of tumors has been suggested (31,33,34). P-selectin expressed on activated endothelium contributes to the rolling of leukocytes that can result in their arrest and extravasation.…”
Section: Biochemistry For the Article ''Functional Transitions In Mymentioning
confidence: 99%
“…E-, P-, and L-selectins are vascular receptors for certain normal sialyl Lewis x/a containing mucin-type glycoproteins found on leukocytes and endothelium (40)(41)(42)(43). Because selectins can mediate tumor cell interactions with platelets, leukocytes, and endothelium in vitro (39,44,45), an in vivo role for selectins in the metastatic spread of tumors has been suggested (31,33,34). P-selectin expressed on activated endothelium contributes to the rolling of leukocytes that can result in their arrest and extravasation.…”
Section: Biochemistry For the Article ''Functional Transitions In Mymentioning
confidence: 99%
“…Platelets have been reported to bind to small cell lung and colon carcinoma via P-selectin (11,12,31,39). Alternatively, platelets may attach to certain melanoma, breast, and colon cancer cells through the integrin receptor ␣ IIb ␤ 3 on the platelet surface (4, 40 -43).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that platelets interact with a number of tumor cell lines, but the cell adhesion experiments were conducted exclusively under static conditions (11,12,31). To determine whether COLO320 cells also adhere to platelets under flow conditions and to determine the role of P-selectin on platelets in the process of cell adhesion, tumor cells were perfused through a parallel plate flow chamber whose lower plate was coated with a layer of platelets.…”
Section: Modified Heparins Inhibit Colo320 Cells Adhering To Surface-mentioning
confidence: 99%
“…Selectins are vascular cell adhesion molecules that recognize certain sialyl Lewis x/a carrying mucin-type glycoproteins found on normal leukocytes and endothelium (11,(19)(20)(21)(22)(23). Carcinoma cell surface molecules carrying sialyl Lewis x/a also can be recognized by all three selectins (11-15, 17, 24-27), mediating tumor cell interactions with platelets, leukocytes, and endothelium in vitro (10,25,27,28). Based on such data, an in vivo role for E-and P-selectins in metastatic spread has been suggested.…”
mentioning
confidence: 99%